A participatory filmmaking process with children with disabilities in rural India: Working towards inclusive research. Issue 3 (November 2019) - Benjamin-Thomas, Tanya Elizabeth; Laliberte Rudman, Debbie; Gunaseelan, Jeshuran; Abraham, Vinod Joseph; Cameron, Debra; McGrath, Colleen; Vinoth Kumar, Samuel Prasanna
Children with disabilities often experience exclusion within their communities, and this exclusion can extend into research processes. The United Nations Convention on the Rights of the Child, however, emphasizes that children of all abilities need to be involved as decision makers in matters affecting them. This article provides an in-depth description of the process of a participatory action research project carried out with children with disabilities from a rural village in India. It argues for the utility of participatory filmmaking as a research methodology that supports inclusion of children with disabilities as co-researchers in research and action processes. The different phases of the research project, namely the preparatory, participatory research, and the action phase, are made transparent along with the details of activities carried out within each phase. The technical and pragmatic challenges faced within this participatory filmmaking process are pointed out, and strategies used to negotiate challenges and adapt this methodology to fit context-specific needs are shared. This account of the complex, yet flexible and adaptable, participatory filmmaking process is presented as means to support critical and informed uptakes of participatory filmmaking for inclusive research practices with children with disabilities.